2020
DOI: 10.3390/genes11030343
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of AhGLK1b (GOLDEN2-like Transcription Factor) in Arabidopsis Confers Dual Resistance to Fungal and Bacterial Pathogens

Abstract: GOLDEN2-LIKE (GLK) is a member of the myeloblastosis (MYB) family transcription factor and it plays an important role in the regulation of plastid development and stress tolerance. In this study, a gene named AhGLK1b was identified from a cultivated peanut showing down-regulation in response to low calcium with a complete open reading frame (ORF) of 1212 bp. The AhGLK1b has 99.26% and 96.28% sequence similarities with its orthologs in Arachis ipaensis and A. duranensis, respectively. In the peanut, the AhGLK1b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The GARP family of Myb TFs includes GLK TFs, which was linked to chloroplast formation in plants ( Chen et al, 2016 ). GLK genes have been discovered and recognized in various higher plants, and studies have found that they play a crucial role in plant resistance to several abiotic and biotic stresses ( Ali et al, 2020 ). In this study, the overexpression of the GhGLK1 gene in A. thaliana and VIGS in cotton was performed to validate the function of this gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GARP family of Myb TFs includes GLK TFs, which was linked to chloroplast formation in plants ( Chen et al, 2016 ). GLK genes have been discovered and recognized in various higher plants, and studies have found that they play a crucial role in plant resistance to several abiotic and biotic stresses ( Ali et al, 2020 ). In this study, the overexpression of the GhGLK1 gene in A. thaliana and VIGS in cotton was performed to validate the function of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…NbGlk1 cooperates with Rx1 gene and facilitates antiviral reaction against potato virus in tobacco ( Nicotiana benthamiana ) ( Townsend et al, 2018 ), AtGLK1 has been discovered to improve cucumber mosaic virus resistance ( Han et al, 2016 ) and in rice, the OsGLK1 gene is important for disease resistance ( Jarvis and López-Juez, 2013 ). AhGLK1b has the potential to provide double tolerance to fungi and bacterial infections and abiotic stress resistance ( Ali et al, 2020 ). Previous reports ( Powell et al, 2012 ) stated that overexpression of GLK increased photosynthesis gene profiling in fruits and chloroplast formation, ensuing in improved carbohydrate and carotenoid in tomatoes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other crops, the peanut is affected by several bacterial, fungal, and viral pathogens ( Ali et al, 2020 ). To manage these pathogens, nature has provided peanuts with several defense mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Although bacterial wilt has been well studied in other plants, there are few studies in peanut, and current research mainly focused on transcriptome change after R. solanacearum inoculation and resistance marker screening ( Chen et al, 2014 ; Luo et al, 2019 ). Up to now, some quantitative trait locus (QTLs) and resistance genes (e.g., AhRLK1 , AhRRS5 , and AhGLKb ) against bacterial wilt have been identified in peanut ( Zhang et al, 2017 , 2019 ; Ali et al, 2020 ), but the molecular mechanism of peanut– R. solanacearum interaction is still poorly understood. The main reasons for this are that the peanut plant itself is not easy to conduct molecular experiments with, and it is the lack of specialized and in-depth research on the pathogenic bacteria causing peanut bacterial wilt.…”
Section: Introductionmentioning
confidence: 99%